The Effect of Concept Map on Academic Achievement of Thinking and Media Literacy Course - Malekzadeh, Nabiollah (2020)
This paper aimed to study the effect of education based on concept map on the academic achievement of secondary school male students in the field of thinking and media literacy. Quasi-experimental research method was used with experimental and control groups. Three classrooms were selected by purposive sampling method (one concept map presentation class, one concept map presentation and construction class and one control class) by random arrangement. In the group of presentation and construction (combined), the course materials were presented to the learners in the form of a concept map. The experimental groups were trained separately for 8 sessions by the teacher-made and combined concept map method and the control group was trained by the traditional method. All groups completed the teacher-made test of academic achievement at two levels of knowledge and perception (understanding). The measuring instrument validity using S. H. Lawshe formula was 0.79 and the reliability of this instrument was 0.807 using Kuder-Richardson. Findings of covariance analysis showed that the mean scores of post-tests of all three groups increased in compared to the pre-tests, but the most effect was observed in the presentation and construction of concept man (combined) group and the least effect was in the control group. Therefore, teaching by a concept map has led to an increase in students' scores.